2020
DOI: 10.3892/or.2020.7917
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA CASC15 facilitates esophageal squamous cell carcinoma tumorigenesis via decreasing SIM2 stability via FTO‑mediated demethylation

Abstract: Long non-coding RNAs (lncRNAs) are involved in the regulation of esophageal squamous cell carcinoma (ESCC) progression. However, the function and mechanism of lncRNA cancer susceptibility candidate 15 (CASC15) are poorly defined. In the present study, tumor and normal adjacent tissues were collected from 45 patients with ESCC. Expression levels of CASC15, fat mass and obesity-associated (FTO) protein and single-minded 2 (SIM2) were examined via reverse transcription-quantitative PCR and western blot assays. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Accumulated researches have focused on the functions and mechanisms of lncRNAs to discover novel diagnostic markers and therapeutic targets for cancers [ 63 66 ]. In this study, a large number of lncRNAs were identified to be expressed aberrantly through transcriptomic analysis of ESCC tumor samples and matched normal tissues, of which LUCAT1 [ 45 ], CASC15 [ 47 ], MIAT [ 48 ], ZNF503-AS1, [ 67 ] and STXBP5-AS1 [ 68 ] have been shown to either promote or inhibit tumorigenesis in ESCC as well as other malignant tumors. In particular, the high expression of LINC00680, AC092910.3, MIR4435-2HG, and GSEC were found to be correlated with poor prognosis in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated researches have focused on the functions and mechanisms of lncRNAs to discover novel diagnostic markers and therapeutic targets for cancers [ 63 66 ]. In this study, a large number of lncRNAs were identified to be expressed aberrantly through transcriptomic analysis of ESCC tumor samples and matched normal tissues, of which LUCAT1 [ 45 ], CASC15 [ 47 ], MIAT [ 48 ], ZNF503-AS1, [ 67 ] and STXBP5-AS1 [ 68 ] have been shown to either promote or inhibit tumorigenesis in ESCC as well as other malignant tumors. In particular, the high expression of LINC00680, AC092910.3, MIR4435-2HG, and GSEC were found to be correlated with poor prognosis in ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…CASC15 targets single-minded 2. lncRNA cancer susceptibility candidate 15 (CASC15) (Figure 4 and Figure 6F) has been shown to be increased in ESSC tissues (130). CASC15 knockdown decreased proliferation and promoted apoptosis in Eca109 and KYSE450 ESCC cells in vitro.…”
Section: Lncrnas Targeting Further Componentsmentioning
confidence: 99%
“…In a similar study, the lncRNA GAS-AS1 was found to promote the ALKBH5-dependent demethylation of GAS mRNA and inhibit cervical cancer proliferation ( Wang et al, 2019 ; Chen et al, 2020 ). Additionally, the lincRNA CASC15 is thought to recruit the demethylase FTO to SIM2, decreasing SIM2 mRNA stability and promoting esophageal cancer progression ( Qin et al, 2020 ). Furthermore, specific lncRNAs such as CACNA1G-AS1 and ACAP2-IT1 have been predicted to regulate m 6 A readers and writers expression ( Zheng et al, 2021 ).…”
Section: Lncrnas Chromatin Remodeling and M 6 A Me...mentioning
confidence: 99%